CAMPUR KODE BAHASA PERANCIS DALAM NOVEL THE CHOCOLATE HEART KARYA LAURA FLORAND - Rahmasari, Nursyahbani Laily; Latjuba, Ade Yolanda; Masdiana, Masdiana (JURNAL ILMU BUDAYA, 2017)
This research aims to find the code-mixing of French language in the dialogue anddescriptions of the English novel. The data were found then analyzed using pragmaticapproach to help explaining the code-mixing. The result of this research indicate that thecode-mixing takes form of a reference of person, reference of food and drink, reference ofexpressive speech (positive) and expressive speech (negative). And based on the context, thecode-mixing refers to some of the context, such as: respect, satire, welcoming and empathy.There are two factors causing the code-mixing, i.e. linguistic factors consisting of noequivalent, French language fluency and clarify the intent of the author. And theextralinguistic factor is the social role of the speakers.Keywords: code-mixing, reference, bilingual, French